Classical Biological Control of Tropical Soda Apple in the USA - Julio C. Medal; James P. Cuda; D. Gandolfo (EDIS, 2002)
This document is ENY-824, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2002.